Boundary element formulations for elastoplastic stress analysis problems - Gun, Halit (1997)
This thesis presents an advanced quadratic formulation of the boundary element (BE) method for two-dimensional elasto-plastic analysis in which 3-node isoparametric quadratic elements are used to model the boundary and 8-node isoparametric quadrilateral quadratic elements are used to model the interior domain.